A study of onychomycosis in Krishna district of Andhra Pradesh, India - Dusi Ratna Harika; Anaparthy Usharani (Our Dermatology Online, 2015)
Introduction: Onychomycosis is a chronic infection of nails caused by fungi such as dermatophytes, yeasts or nondermatophyte moulds. It is the most prevalent of all the nail ailments and affects 3- 5% of the population worldwide and represents 20-40% of onychopathies and about 30% of mycotic cutaneous infections. Aims: 1)To isolate and identify the etiological fungi and to assess the prevalence of onychomycosis. 2)To analyse the epidemiological and mycological features of onychomychosis. Methods: 109 nail samples were collected from 102 clinically suspected cases of onychomycosis and further analysed. Results: Of 102 cases, the commonest age group was 41-50 years 38 (37.25%); males were 63 (61.76%) and females 39 (38.24%); involvement of toe nails in 73 (71.57%), finger nails 25 (24.51%) and both 4 (3.92%); 56 (54.90%) belonged to low socio-economic status, middle 31 (30.39%) and high 15 (14.71%). Labourers were 14 (13.73%), farmers and office personnel 10 (9.80%). Of 109 samples, direct microscopy by KOH mount was positive in 82 (75.23%) and fungal culture in 52 (47.71%) of which 29 (26.61%) yielded dermatophytes, NDM's 11(21.15%), Candida spp. 8 (15.38%) and mixed growth 4 (7.68%). Dermatophytes 25(48.08%) were the predominant group isolated from toe nails and Candida spp. 6 (11.54%) from the finger nails respectively. Among the 56 isolates, dermatophytes were the predominant group 31 (55.36%) followed by NDM's 15 (26.78%) and Candida spp.10 (17.86%). Conclusion: Onychomycosis is a frequent cause of nail infection. The mycological study and the identification of etiological agents of onychomycosis are needed to confirm the clinical diagnosis and for the choice of therapy